2007
DOI: 10.1007/s10735-007-9096-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent parathyroid hormone (PTH) administration on SOST mRNA and protein in rat bone

Abstract: Sclerostin, the secreted protein product of the SOST gene, which is mainly expressed by osteocytes, has recently been proposed as a negative regulator of bone osteoblastogenesis. Chronic elevation of PTH reduces SOST expression by osteocytes, while controversial results have been obtained by intermittent PTH administration. We have investigated the effects of intermittently administered PTH on SOST expression and sclerostin localization, comparing them with those of controls, as they appeared in three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 29 publications
5
72
0
Order By: Relevance
“…At least some of the positive effects of parathyroid hormone on bone formation have been attributed to its ability to moderately down-regulate sclerostin (32)(33)(34). The inability of Scl-AbI to prevent DEXinduced inhibition of growth is therefore consistent with the findings from a study by van Buul-Offers et al (35), in which they showed that parathyroid hormone was also ineffective at reducing GC-mediated growth inhibition (36).…”
Section: Discussionsupporting
confidence: 73%
“…At least some of the positive effects of parathyroid hormone on bone formation have been attributed to its ability to moderately down-regulate sclerostin (32)(33)(34). The inability of Scl-AbI to prevent DEXinduced inhibition of growth is therefore consistent with the findings from a study by van Buul-Offers et al (35), in which they showed that parathyroid hormone was also ineffective at reducing GC-mediated growth inhibition (36).…”
Section: Discussionsupporting
confidence: 73%
“…Another osteocyte-derived factor, sclerostin, is a glycoprotein encoded by the SOST gene [10], and was reported to bind the LRP5/6 receptor, thereby antagonizing Wnt signaling and increasing -catenin degradation [11,12]. Sclerostin has been reported as a negative regulator of osteoblastic bone formation [12][13][14][15]: Sclerostin secreted by osteocytes may pass through the osteocytic canaliculi and inhibit bone-lining osteoblasts. Taken together, osteocytes are not merely resting cells embedded in bone, but appear to be dynamically related to bone metabolism, e.g., by secreting sclerostin.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports showing that periosteal mesenchymal cells respond to locally increased levels of growth factors and cytokines, and may differentiate into chondrocytes or osteoblasts (41), so that, the periosteal mesenchymal environment appears to influence such cell fate (4). In spite of the local ef-blastic bone formation (27,31,36), as it is secreted by osteocytes, passes through the osteocytic canaliculi and inhibits the activation of bone-lining osteoblasts. On the other hand, there are reports on FGF23-driven modulation of adequate serum phosphate concentrations, which are required for normal skeletal development as well as preservation of bone integrity (28).…”
mentioning
confidence: 99%